NEUROBLASTOMA IN ADULT: CASE REPORT AND LITERATURE REVIEW - E. A. Skorniakova; L. G. Zaslavskii; N. A. Neofidov; S. L. Vorobev; A. A. Gotovchikov; O. V. Rodionova; A. G. Kovelenov; O. L. Zaslavskaia (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2018)
Neuroblastoma is a malignant tumor derived from the neuroblasts of the sympathetic nervous system, which develop in any region of the nervous system. Usually, neuroblastoma is detected in children aged 1–2 years. About 90% of cases are diagnosed before the age of 5 years. The incidence of adult neuroblastoma is only 0.3 cases per million people per year. The clinical course and biological activity of adult neuroblastoma is different than children neuroblastoma. Early diagnosis of this disease in adults is necessary for timely start of treatment and increasing life expectancy. In this clinical observation, we present a detailed description of the course of this rare disease in the 34-year-old male and literature review on adult neuroblastoma.